De koepelgevangenissen van J.F. Metzelaar (1886). Een onderzoek naar de herkomst van de ronde vorm (Bulletin KNOB, 2006)
When the first Dutch Criminal Code was introduced in 1886, cellular imprisonment, during five years at most, was adopted as the Standard form of detention. The lack of cells resulting from it was solved by the building of three new cellular prisons, including the two identical buildings in Arnhem and Breda. These were built by J.F. Metzelaar (1818-1897), who from 1870 was employed at the Dutch Ministry of Justice as 'Engineer-Architect for prisons and court houses'. Unlike frequently assumed, the striking round form of these prisons was not so much inspired by the eighteenth-century ideal model of the panopticon, as by a striving for improvement of the already existing cellular wing-shaped prisons in Amsterdam (1849), Utrecht (1856), Rotterdam (1872) and Groningen (1884).The Christian 'Society for the Moral Improvement of Prisoners', founded in 1823 and in the course of time developing into an authoritative and respected advisory body of the government, kept a close track of the cellular building of prisons. It stressed the importance of religion within the prison, which - combined with solitary confinement - it considered necessary in order to reform sinful, guilty and depraved creatures with God's help. It considered that a chapel was required for the practice of religion, whereby the prisoners would be in separate booths (so-called 'stalls'), for which reason the chapel was also called 'stalls church'. Although these religious celebrations did not take place frequently, only on Sundays and public holidays, its effect on the prisoners was thought to be far-reaching.The situation of this 'stalls church' within the wing-shaped prison proved to be problematic. In his pursuit of perfecting the cellular system Metzelaar decided to apply a new type of prison, also because of the fact that within the wing-shaped prison no suitable location could be found for the 'stalls church'. The responsible Minister of Justice, A.E.J. Modderman, who was a minister as well as special commissioner of the Society, also considered a correct practice of religion of great importance. Apart from the fact that the round floor plan would bring about large improvements in the field of surveillance and isolation of the prisoners, according to Metzelaar it would also make the building of a separate chapel unnecessary. During the religious practice the clergyman was in the middle of the round central hall, on top of the inspection post. Consequently, the prisoners did not need to leave their cells, which were situated on the outside of the large round central hall. By opening the food-hole in the cell door they could follow the service. Thus staff and building costs could be economized on. Due to disappointing results - the clergyman could hardly make himself heard because of the resonance - a few years later a separate stalls church was added on the grounds after all. Nevertheless, in 1901 a third round prison was built in Haarlem, designed by his son, W.C. Metzelaar.